Training Agricultural Research & Extension Staff to Produce and Communicate Agro-Climatic Information, to Enhance the Resilience and Food Security of Farmers and Pastoralists in Kiteto, Tanzania: Preliminary Findings from the GFCS Adaptation Programme in Africa - Dorward, P.; Tall, Arame; Kaur, Harneet; Hansen, James (2014)
National Agricultural Extension Systems in ten districts in Tanzania and Malawi are receiving training in the production and use of climate services as part of a WFP-CCAFS joint activity within the GFCS Adaptation Programme in Africa. This document reports on the first training of intermediaries, conducted for 30 agricultural extension and NGO staff from Kiteto District, Tanzania, 13-17th October 2014 and draws lessons from this to feed forward into preparation and training in the remaining districts in 2015. Preparation for the course included analysis of historical climate information, as well as training of staff from the Tanzania Meteorological Agency in downscaling using the Climate Prediction Tool (CPT). The ensuing training course for intermediaries covered the Participatory Integrated Climate Services for Agriculture (PICSA) approach. This aimed to equip agricultural extension field staff to provide local historical climate information, seasonal and sub-seasonal forecasts (seamless forecasts) together with crop and livelihood information and to facilitate use of participatory decision making tools by smallholder farmers, in order to enhance farm and field-level decision making for resilience and food security. Training included a strong practical component. At the end of the training course agricultural extension officers and NGO staff developed plans for implementation in the locations that they work. Formal and informal feedback from participants was very positive. From this first training several improvements to feed into subsequent training in Tanzania and Malawi were identified and recommendations are made. These include: how to ensure that climate information for districts is analysed well in advance; appropriate crop and livestock management options are identified to cover variation within each district; climatic variability is adequately addressed within districts; and the potential benefits of CPT downscaled forecasting are fully explored.